8 Gatekeeping the cath lab: evaluating practice in the revised nice guideline era. (May 2018) - Kehagia, Angie A; Scully, Paul R; Tarkin, Jason; Menezes, Leon J
Abstract : Introduction: We performed a service evaluation as the first stage of a quality improvement project to assess the use of gatekeeper tests prior to cardiac catheterisation in patients with suspected stable chest pain, prior to and after the introduction of the revised NICE Clinical guidelines. Methods: A retrospective review over 14 days at two time points, Nov/Dec 2016 and Nov/Dec 2017, of cath labs activity via the Electronic Health Record. Data were collected on the referral reasons, whether and which gatekeeper tests had been performed within 1 year of the invasive procedure, and whether and what kind of revascularisation ensued. Results: A total of 151 catheterisation cases were assessed. 99 were excluded on the basis of presenting with acute coronary syndrome or catheterisation being planned as part of a staged procedure or research. Mean age: 61.8 years (SD 11.3 years). 32.7% female. More gatekeeping tests were performed in 2017 (72%) compared to 2016 (48.1%) [X 2 (1, n=52)=3.01, p=0.08]. 33% and 48% [p>0.27] of cases in 2016 and 2017 respectively had subsequent revascularisation. Across both time-points, 14/52 patients (26.9%) underwent neither gatekeeper test nor revascularisation. CTCA was used much more as a gatekeeper test in 2017. Conclusion: A year after the NICE guideline update, 36% of cases had not undergone appropriate gatekeeper testing. 27% of all cases underwent neither gatekeeper test nor subsequent revascularisation. The increased use of CTCA in 2017 is in line with the predicted rise in CT referrals as per the new guidelines. This change has implications for service provision.